KEPUASAN PEMANGKU KEPENTINGAN DARI PERAN LEMBAGA MASYARAKAT PELESTARI PADI PANDANWANGI CIANJUR - Endah Lisarini; Ayi Khobul Nuryana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
The existence of a farmer in Indonesia will be stronger when joining a farming group or organization. The activities of agricultural institutions in Indonesia are directed to the development of food crops, especially rice, including Cianjur, West Java. The Pandanwangi Cianjur Rice Conservation Society (MP3C) is an agricultural institution that plays an active role in developing and preserving Pandanwangi rice as a variety of Geographical Indications. The existence of MP3C will be seen from stakeholder satisfaction with its role. This research was conducted with the aim of reviewing: 1). How is the existence and role of the MP3C; 2). How much stakeholder satisfaction is there for the role and performance of MP3C. 35 responses were collected from respondents consisting of Pandanwangi farmers, Pandanwangi rice traders and consumers, government and academics. Determination of respondents as samples is done by quota sampling technique. There are 5 dimensions to measuring satisfaction with the performance and interests of MP3C institutions. These dimensions include tangible, reliability, responsiveness, assurance and empathy. To answer the objectives of the first research qualitative descriptive analysis was carried out on the respondents' information and responses. The second research objective was answered by the analysis method of the Customer Satisfaction Index (CSI) and Importance and Performance Analysis (IPA). The results of the study indicate: 1) The existence of MP3C institutions is very important for stakeholders. MP3C has a role in controlling, overseeing, supervising and fostering the Pandanwangi rice farmers who are members; 2) The role of MP3C is considered very important by stakeholders in terms of guidance and counseling, while the performance of MP3C is considered to provide satisfaction with the CSI value of 69.93%. Such a condition is expected to be a consideration for the continuous improvement and sustainability of the MP3C institution in an effort to develop and preserve Pandanwangi rice.